Pengaruh Pemberian Pupuk Kandang Kambing Dan Pupuk Za Terhadap Sifat Kimia Lahan Bekas Sawah Dan Produksi Bawang Merah (Allium ascalonicum L.) - Andriau Matius Sinaga; Posma Marbun; Alida Lubis (Jurnal Agroekoteknologi, 2019)
The effect of giving goat manure and ZA fertilizer on the chemical properties of paddy soil and red onion production (Allium ascalonicum L.). The purpose was to determine the effect of goat manure and ZA fertilizer on the chemical properties and production of red onion on paddy fields. This research was conducted from April to June 2018 using factorial randomized block design (RBD) and repeated three times. The first factor is the dose of goat manure consisting of: 0, 2.5, 5, 7.5 tons / ha, and the second factor is the dose of ZA fertilizer consisting of: 0, 200, 400, 600 kg / ha. The results showed that the application of goat manure significantly affected the increase of C-organic, cation exchange capacity. ZA fertilizer has a significant effect on pH reduction.